LIQUIDITY, PROFITABILITY, AND CAPITAL STRUCTURE: THEIR ROLE IN SHAPING FIRM VALUE IN FOOD & BEVERAGE (2021–2023) - Nur Indah Novita Dama; Hais Dama; Mohamad Agus Salim Monoarfa (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of liquidity, profitability, and capital structure on firm value in Food and Beverage companies listed on the Indonesia Stock Exchange during 2021–2023. Firm value is proxied by Price to Book Value (PBV) and Tobin’s Q. Liquidity is measured using Current Ratio (CR) and Quick Ratio (QR), profitability is measured using Return on Assets (ROA) and Return on Equity (ROE), while capital structure is measured using Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). This research employed a quantitative approach using secondary data obtained from annual financial reports of Food and Beverage companies listed on the Indonesia Stock Exchange The sampling technique used in this study was purposive sampling, with a sample size of 38 companies. Data were analyzed using multiple linear regression with classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results show that CR has a positive and significant effect on PBV and Tobin’s Q. QR has a negative and significant effect on PBV, but no significant effect on Tobin’s Q. ROA has a positive and significant effect on both PBV and Tobin’s Q. ROE has a positive and significant effect on PBV, but a negative and significant effect on Tobin’s Q. DAR has a negative and significant effect on PBV, but no significant effect on Tobin’s Q. DER has no significant effect on both proxies of firm value. Simultaneously, liquidity, profitability, and capital structure significantly affect firm value. These findings indicate that firm value is determined by the combined role of financial stability, profitability, and financing decisions.